PENGARUH SHIFT KERJA TERHADAP IKLIM KESELAMATAN YANG DI MEDIASI OLEH MASALAH TIDUR DAN KELUHAN KESEHATAN PADA KARYAWAN JASA TRANSPORTASI ANGKUTAN DARAT PENUMPANG PADA TERMINAL TYPE B BANDA ACEH - Ayuni Sakinah, Ade Irma Suryani (Departemen Manajemen, 2017)
This study aimed to measure the “Effect of Shift Work in Mediation By Sleep Problems and Complaints In Employee Health Services Land Transport Transportation Passenger Terminal Type B Banda Aceh”. The sample used in this study is the driver's status as employees totaling 104 respondents. Equipment collecting data used in this study was a questionnaire. The sampling technique used is probality Sampling (HLM) is used as a method of analysis to determine the effect of all the variables involved. The results showed: 1) Shift Work Safety positive effect on climate. 2) Shifts positive effect on sleep problems. 3) Shifts positive effect on health complaints. 4) Sleep Problems positive effect on safety climate. 5) Health Complaint positive effect on safety. 6) Sleep Problems and Complaints Pemediasi Health as a positive influence on Variable Shifts and Safety Climate on Land Transport Transportation Driver Passenger Terminal Type B Banda Aceh. Keywords: Shift Work, Climate Safety, Sleep Problems, Complaints Health